Modern Japan : a very short introduction - Goto-Jones, Christopher S. (Very short introductions., 2009)
From the Publisher: Japan is arguably today's most successful industrial economy, combining almost unprecedented affluence with social stability and apparent harmony. Japanese goods and cultural products-from animated movies and computer games to cars, semiconductors, and management techniques-are consumed around the world. In many ways, Japan is an icon of the modern world, and yet it remains something of an enigma to many, who see it as a confusing montage of the alien and the familiar, the ancient and modern. This Very Short Introduction explodes the myths and explores the reality of modern Japan, offering a concise, engaging, and accessible look at the history, economy, politics, and culture of this fascinating nation. It examines what the term "modern" means to the Japanese, debunks the notion that Japan went through a period of total isolation from the world, and explores the continuity between pre- and post-war Japan. Anyone curious about this intriguing country will find a wealth of insight and information in these pages